A Timely Musical Discourse, or A Music Treatise from Lost Times, Part I - Bonus, Alexander (Current Musicology, 2013)
Eschewing some serious scholarly reservations, I wish to present a significant portion of a heretofore unknown treatise that concerns the nature of musical time. It takes the form of a dialogue between two musicians, a teacher and his student. The characters might represent actual musicians, or perhaps they personify two entirely contrasting musical cultures. In all likelihood, they are both fictional. Yet if we take their discussion as an allegorical representation of a fundamental rift in the understanding of musical time, then the characters seem to function as every–musicians, who offer a variety of arguments in support of fundamentally oppositional stances. Their wandering discussion, as is typical of the Socratic style, nevertheless revolves around a central thesis. What quickly comes to the fore is the teacher’s assertion that objectivist ideals regarding temporality fail to reflect complex performance practices from past Western traditions.